Odpowiedzi

2009-11-25T17:43:46+01:00
A)
2x+2y=8
2x-y=-4 /x2

2x+2y=8
2x-2y=-8

4x=0 /:4
x=0

x=0
2y=8 /:2

x=0
y=4
(0,4)
2009-11-25T17:47:36+01:00
A)podziel przez 2 to: x+y=4 x=4-y

podstaw x
2(4-y)-y=2
8-2y-y-2=0
6=3y
y=2
x=2
b)podziel przez 2 to 3x-y=1 to 3x-1=y
podstaw za y
2x-3(3x-1)=-4
2x-9x+3+4=0
7=2x
x=7/2
c) x=-3y-3
3(-3y-3)y=11

d) x=3y-3
2(3y-3)+y=-6
6y-6+y=-6
7y=0
y=0
x=-3
2009-11-25T18:10:48+01:00
A) 2x+2y=8
2x-y=2 /*(-1)

2x+2y=8
-2x+y=-2
_________
3y=6 /:3
y=2

2x+2y=8
2x+2*2=8
2x+4=8
2x=8-4
2x=4 /:2
x=2

y=2
x=2



b) 6x-2y=2
2x-3y=-4 /*(-3)

6x-2y=2
-6x+9y=12
___________
7y=14 /:7
y=2

6x-2y=2
6x-2*2=2
6x-4=2
6x=2+4
6x=6 /6
x=6


c) x+3y=-3
3x-y=11

x=-3-3y
3(-3-3y)-y=11

x=-3-3y
-6-6y-y=11

x=-3-3y
-6-7y=11

x=-3-3y
-7y=11+6

x=-3-3y
-7y=17 /:(-7)

x=-3-3y
y=-2³₇

x=-3-3*(-2³₇)
y=-2³₇

x=-3+7²₇
y=-2³₇

x=4²₇
y=-2³₇



d)3y=x+3
2x+y=-6

-x=3-3y
2(3-3y)+y=-6

-x=3-3y
6-6y+y=-6

-x=3-3y
-5y=-6-6

-x=3-3y
-5y=-12 /:(-5)

-x=3-3y
y=2²₅

-x=3-3*2²₅
y=2²₅

-x=3-7¹₅
y=2²₅

-x=-4¹₅ /:(-1)
y=2²₅

x=4¹₅
y=2²₅